Potensi Senyawa Bioaktif Ekstrak Kasar Bakteri Simbion Spons sebagai Anthelmintika : Sebuah Uji Pendahuluan - Muhammad Reza Faisal; Mujizat Kawaroe; Fadjar Satria (Journal Omni-Akuatika, 2014)
This study aims to observe the bacterial symbionts of sponge and determine chemical compounds profile in the crude extract of bacterial isolates then to determine the lethal toxicity values (LC50-24 hours) as a preliminary anthelmintic test. The method consisted of the identification of gram staining, organic solvent extraction,  phytochemical screening  and  toxicity  assay  by  the  Artemia  salina  LC50-24  hours.  The concentration used consisted of 10 µg / ml; 100 µg / ml; 250 µg / ml; 500 µg / ml. Results showed isolate SC12 (2) C and S1-2 (1) belonging to the gram-positive where the bioactive compounds i.e. flavonoids and triterpenoids obtained from the crude extract were predominant. The minimum concentrations from toxicity tests were  35.11 µg/ml for isolate SC12(2)C and 41.2 µg/ml for S1-2 (1). The crude extract of both isolates showed potential as a anthelmintic compound with concentration LC50-24 hours <1000 mg/ml.Keywords : Bacterial symbionts sponge, S12(2) C, S1-2 (1), Phytochemicals, toxicity, Anthelmintic.